Effects of arbuscular mycorrhiza inoculation on growth and yield of tomato (Lycopersicum esculentum Mill.) under salinity stress - Damaiyanti, D R R; Aini, N; Soelistyono, R (Journal of Degraded and Mining Lands Management, 2015)
Objective of the research was to study the effect mycorrhiza on growth and yield of tomato. The experiment was conducted in screen house 14 m x 10.5 m, in Pasuruan on November 2013 until March 2014, The experiment was conducted as a factorial randomized complete design. The first factor was dose of mycorrhiza (without mycorrhiza, 5 g mycorrhiza, 10 g mycorrhiza, and 20 g mycorrhiza). The second factor was the salinity stress level (without NaCl, 2500 ppm NaCl, 5000 ppm NaCl, and 7500 ppm NaCl). The results showed that salinity stress at the level 7500 ppm decreased the amount of fruit by 30.84% and fresh weight per hectare decreased by 51.72%. Mycorrhizal application was not able to increase the growth and yield in saline stress conditions; it was shown by the level of infection and the number of spores on the roots of tomato plants lower the salinity level 5000 ppm and 7500 ppm. But separately, application of 20 g mycorrhiza enhanced plant growth, such as plant height, leaf area, leaf number and proline. Application of 20 g mycorrhiza increased the yield by 35.99% Â